2018
DOI: 10.1177/1478210318806134
|View full text |Cite
|
Sign up to set email alerts
|

The subjectivity offalse hopeand the possibility forcritical hopeamong novice teachers

Abstract: The current neoliberal policy regime that has dictated school reform policies such as standardized testing and performance accountability challenges the professional values of teachers. As a result, they become policy subjects who either accept or resist the neoliberal agenda. Given the high turnover of novice teachers in schools governed by neoliberal policies, this study sought to understand first-year teachers’ feelings of efficacy and career decisions. This paper applies Duncan-Andrade’s (2009) theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
3
0
2
Order By: Relevance
“…The findings of research question 3 could be as a result of the economic degradation and poor attention given to educational institutions in Nigeria. Although this research showed that the presentday graduate teachers demonstrate higher ICT skills for pedagogy, there is little trust in the quality of the teacher for the school system (Duarte, 2019;Ginsburg, 2017). Finally, the outcome of research question 4 showed that there is a 'disconnect' in the interaction between policy, ethics, and quality of graduate teachers in the teacher education programme in Nigeria.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The findings of research question 3 could be as a result of the economic degradation and poor attention given to educational institutions in Nigeria. Although this research showed that the presentday graduate teachers demonstrate higher ICT skills for pedagogy, there is little trust in the quality of the teacher for the school system (Duarte, 2019;Ginsburg, 2017). Finally, the outcome of research question 4 showed that there is a 'disconnect' in the interaction between policy, ethics, and quality of graduate teachers in the teacher education programme in Nigeria.…”
Section: Discussionmentioning
confidence: 86%
“…According to Okafor and Chukwuedo (2015, p. 59), "educational policy is a fundamental document that must guide the smooth running of any educational programme". In the context of the teacher education programmes, this policy promotes effective and efficient teaching-learning processes, management of teaching/learning resources (Duarte, 2019;Toby, 2000), administrative routine (Nwadiani, 2011;Olubor, 2004) and behavioural conducts (Ogbonnaya, 2010) of learners, teaching and non-teaching members of staff of the school system. In its attempt to control behavioural conduct, a policy may be a guide to promoting ethical practices in the educational sector; hence, this research theorized that policy has a connection with ethical practices in the school system as well as the quality of graduate teachers.…”
Section: Research Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…Enfin, l'espoir reporté, ou hope deferred , cache un certain désespoir et fait en sorte que le personnel scolaire pousse les élèves à reporter à plus tard leur rêve d'amélioration de leurs conditions, dans un avenir non défini (Duncan‐Andrade, 2009 ). Une étude empirique récente indique que l'espoir à l'eau de rose, l'espoir mythique et l'espoir reporté sont fort répandus dans les récits d'enseignant.e.s qui font référence tant aux piliers de l'espoir critique qu'aux faux espoirs (Duarte, 2019 ).…”
Section: Le Cadre Théoriqueunclassified
“…Enfin, l'espoir reporté, ou hope deferred, cache un certain désespoir et fait en sorte que le personnel scolaire pousse les élèves à reporter à plus tard leur rêve d'amélioration de leurs conditions, dans un avenir non défini (Duncan-Andrade, 2009). Une étude empirique récente indique que l'espoir à l'eau de rose, l'espoir mythique et l'espoir reporté sont fort répandus dans les récits d'enseignant.e.s qui font référence tant aux piliers de l'espoir critique qu'aux faux espoirs(Duarte, 2019).Duncan-Andrade (2009) propose trois piliers de l'espoir critique : l'espoir matériel (material hope), l'espoir socratique (socratic hope) et l'espoir audacieux (audacious hope). L'espoir matériel se définit comme toute ressource mise en place pour garantir l'apprentissage et la réussite des élèves, notamment un enseignement de qualité et des attentes élevées à l'égard des élèves(Duncan-Andrade, 2009, p.186).…”
unclassified